Live demonstration : a FSK-OOK ultra wideband impulse radio system with spontaneous clock and data recovery - Chen, Shoushun (2013)
We present a non-coherent wireless communication testing platform for ultra wide-band impulse radio (UWB-IR) with frequency-shift-keying (FSK) on-off-keying (OOK). Both transmitter and receiver platform will be present with a control graphic user interface (GUI) supported by Spartan-3 FPGAs. The transmitter chip is integrated while the receiver is build from off-the-shelf components. Monopole antennas are used in the system. The demonstration shows a transformative wireless communication technology for low power low cost short range applications.